1976
DOI: 10.1159/000180669
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plasma Calcium on Plasma ADH Levels in Anephric Patients

Abstract: Ten anephric patients were studied before and during hemodialysis. The extracorporeal circuit was primed with 5% albumin in 0.9% sodium chloride. Ultrafiltration volume removed by the hemodialyzer was replaced continuously. Modifications of a standard chronic renal failure dialysate were used to minimize changes in plasma urea while varying plasma sodium and calcium in opposite directions. Plasma ionized calcium concentrations in two patients confirmed other studies demonstrating a correlation between plasma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…If hypercalcemia produces increased thirst in either man or experimental animal, then chronic polydipsia could result in a wash-out of the medullary osmotic gra dient as well as a physiologic suppression o f endogenous ADH levels [4], However, while increased thirst does appear to occur in patients with hypercalcemic disorders [5], it has been established in experimental animals that restriction o f fluid intake does not attenuate the polyuria o f hypercalcemia and in fact marked dehydration occurs under such conditions [6], Additional evidence against primary polydipsia and suppressed ADH levels as the mechanism for the polyuria is the demonstration o f ele vated plasma osmolality in a number o f hypercalcemic subjects [2], Furthermore, many studies have shown a resistance to exogenously administered vasopressin, sug gesting that even if endogenous vasopressin levels were elevated, polyuria would persist [2], While calcium could act directly on the neurohypophysis to suppress endoge nous ADH secretion, studies in anephric patients on dial ysis have clearly shown that elevations o f calcium level stimulate rather than suppress ADH release [7], Recent studies also suggest that as with many neuroendocrine systems, increases in intracellular calcium levels may have an important influence to increase pituitary ADH release [8], Thus, all o f these observations suggest that either physiologic or pathologic suppression of ADH release does not play an important role in the polyuria of hypercalcemia.…”
mentioning
confidence: 99%
“…If hypercalcemia produces increased thirst in either man or experimental animal, then chronic polydipsia could result in a wash-out of the medullary osmotic gra dient as well as a physiologic suppression o f endogenous ADH levels [4], However, while increased thirst does appear to occur in patients with hypercalcemic disorders [5], it has been established in experimental animals that restriction o f fluid intake does not attenuate the polyuria o f hypercalcemia and in fact marked dehydration occurs under such conditions [6], Additional evidence against primary polydipsia and suppressed ADH levels as the mechanism for the polyuria is the demonstration o f ele vated plasma osmolality in a number o f hypercalcemic subjects [2], Furthermore, many studies have shown a resistance to exogenously administered vasopressin, sug gesting that even if endogenous vasopressin levels were elevated, polyuria would persist [2], While calcium could act directly on the neurohypophysis to suppress endoge nous ADH secretion, studies in anephric patients on dial ysis have clearly shown that elevations o f calcium level stimulate rather than suppress ADH release [7], Recent studies also suggest that as with many neuroendocrine systems, increases in intracellular calcium levels may have an important influence to increase pituitary ADH release [8], Thus, all o f these observations suggest that either physiologic or pathologic suppression of ADH release does not play an important role in the polyuria of hypercalcemia.…”
mentioning
confidence: 99%